On Sarajevo’s Pinkas - Finci, Predrag (Poznańskie Studia Slawistyczne, 2016)
The text presents a story about Pinkas, the record of Jewish Community, confiscated during Second World War by the Nazis. History of Sarajevo’s and Bosnian Jewish Community is covered in Pinkas. The author makes use of existing documents and literature reconstruction of Bosnian history and Sarajevo’s Pinkas itself.